Emission Inventory For Area Source: Case Study In Majlis Bandaraya Melaka Bersejarah (MBMB) Region - Md Isa, Mohamed Hafiz; Tee, Boon Tuan; Zakaria, Muhammad Zulfattah; Zulkafli, Nur Izyan; Rivai, Ahmad; Ab Razak, Juhari; Yusof, Ahmad Anas (National Geographical Association Of Malaysia, 2017)
The aim of this study is to investigate the air pollution emission and develop an emission inventory from area source in Majlis Bandaraya Melaka Bersejarah – Historical Melaka City Council (MBMB) region. The area source covers sources that are small in nature but releases air pollutants over a relatively limit area. In this case study, the area sources are residential cooking facilities, school canteens, petrol stations, car repair/garages, restaurants, open burning areas, and construction sites. The required data are obtained through questionnaire, interviews, and direct observation at sites in the region. Other related information was also obtained from validated and published data by government official publication such as Department of Statistics and Department of Environment (DoE). The calculation procedures and identification of emission factors in developing the emission inventory are based on CORINAIR Air Emission Guidebook 2013. The detailed emission data is then being plotted on the city map. The results show that fuel burning equipment from households and restaurants emitted higher air pollutants than other source categories. Overall, annual emission of Nitrogen Oxides (NOx) was about 100.22 tons/year, Carbon Monoxide (CO) was 748.63 tons/year, Sulphur Oxides (SOx) was 3.35 tons/year, Non-Methane Volatile Organic Compounds (NMVOC) was 197.10 tons/year and Particulate Matters (PM10) was 100.49 tons/year. The results from the emission inventory identified key sources of air pollution for the city will be the basis for the future Melaka City Clean Air Plan (CAP) development.